Iron and slag: contribution of iron data to the history of West African societies - (:unkn) unknown (My University, 2020)
In sub-Saharan Africa, iron industry is the oldest, most widespread and most important of the metallurgies practised there. Three millennia old at least, it is highlighted by African archaeologists to characterize the period between prehistory and the opening of the continent to Western technical influences. But what do we know about this very long period that is sometimes perceived as indefinite and immobile? By using the chronological category "Protohistory" instead of "Pre-colonial Period", archaeologists have sufficiently questioned what this periodization of African history represented. Is there sufficient understanding of the place and role of iron and the craftsmen who produced it in African societies in the periods following its introduction?This research proposes to overcome these pitfalls by developing retrospective maps that answer the following questions: where, when, how, how much and for whom was iron produced in Africa? It is therefore fully inspired by geohistory, which consists in mobilizing the tools of the geographer to compose an explanation of events and periodicities, starting from the hypothesis that the localization of social phenomena is a fundamental dimension of their own logic and that geohistory leads to questioning and historicizing the divisions of the World. At the same time, the production of retrospective maps leads to the identification of all the data relating to a phenomenon and to the evaluation of their qualitative and quantitative relevance.Before embarking on a history of iron in Africa, it is essential to begin by establishing a knowledge assessment that highlights data and methods. The study area chosen follows a north-south transect (Mali, Burkina Faso, Ghana, Togo and Benin) which offers the advantage of freeing itself from identical environmental and political blocks and is one in which I have conducted a great deal of research. The creation of a database containing all the information on iron associated wi
Keywords: African Research